(untitled) (Journal of Social Sciences Review, 2023)
Research on depressogenic cognition has already documented negative cognitive styles and rumination with reference to depressive symptoms. The present study intended to explore the gender differences and interaction effect of rumination and negative cognitive style in predicting depression. The major hypotheses tested were (1) the interaction of negative cognitive styles and SRR predicts depression and (2) gender base differences would exist with reference to RRS and NCS. Study results revealed that both the study variable were significant predictors of depression. Similarly, the interaction effect NCS x RRS significantly predicted depression in a positive direction. Exploring the gender differences, it was found that females experienced more depressed feelings accompanied by a higher magnitude of ruminative response and negative cognitive style.